Analisis Kepercayaan Diri Dan Dukungan Orang Tua Terhadap Motivasi Berprestasi Atlet Klub Bola Voli Livo U-19 Kota Tegal - Dinda Zalfa Sari; Sungkowo Sungkowo (Universitas Hamzanwadi, 2026)
Low self-confidence and limited parental support often hinder adolescent athletes’ motivation to achieve. Research examining these two variables simultaneously among adolescent volleyball athletes at the local club level is still limited. This study aimed to examine the partial and simultaneous effects of self-confidence and parental support on athletes’ achievement motivation. This research employed a quantitative correlational design involving 40 athletes from Livo U-19 Volleyball Club selected through purposive sampling. Data were collected using a Likert-scale questionnaire that had passed validity and reliability testing. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics. The results showed that self-confidence (t = 2.795; sig. = 0.043) and parental support (t = 4.145; sig. = 0.000) had significant effects on achievement motivation. Simultaneously, both variables contributed 37.1% to athletes’ achievement motivation (F = 10.916; sig. < 0.001). The findings indicate that self-confidence and parental support both have significant partial and simultaneous relationships with achievement motivation. Parental support was found to be the most dominant factor in enhancing adolescent athletes’ motivation to achieve, highlighting the importance of positive and active parental involvement alongside the development of athletes’ self-confidence.